Amyloid-beta mediates homeostatic synaptic plasticity - Galanis, Christos; Fellenz, Meike; Becker, Denise; Bold, Charlotte; Lichtenthaler, Stefan; Müller, Ulrike C.; Deller, Thomas; Vlachos, Andreas (The journal of neuroscience, 2021)
The physiological role of the amyloid-precursor protein (APP) is insufficiently understood. Recent work has implicated APP in the regulation of synaptic plasticity. Substantial evidence exists for a role of APP and its secreted ectodomain APPsα in Hebbian plasticity. Here, we addressed the relevance of APP in homeostatic synaptic plasticity using organotypic tissue cultures prepared from APP−/− mice of both sexes. In the absence of APP, dentate granule cells failed to strengthen their excitatory synapses homeostatically. Homeostatic plasticity is rescued by amyloid-β and not by APPsα, and it is neither observed in APP+/+ tissue treated with β- or γ-secretase inhibitors nor in synaptopodin-deficient cultures lacking the Ca2+-dependent molecular machinery of the spine apparatus. Together, these results suggest a role of APP processing via the amyloidogenic pathway in homeostatic synaptic plasticity, representing a function of relevance for brain physiology as well as for brain states associated with increased amyloid-β levels.
Gesehen am 18.08.2021